[Kidnapped ; The Fall of Pagsanjan ; Joseph, the dreamer [videorecording] - Lazaro, Cheche (The Probe Team, 1991)
Takes a look at the abduction of Cochise Bernabe and his girlfriend ; the Department of Tourism ordering a pull-out of promotions for the scenic tourist town of Pagsanjan claiming tratmen cheat tourists and have lost all sense of discipline and morality ; and the presentation of a Christian musicale about Joseph and his seven brothers featuring Christian singers, Audie Gemora and Freddie Santos.